Catalysts for Enhanced CO2-CH4 Exchange in Natural Gas Hydrates. An experimental feasibility study of exchange enhancement by use of chemical additives - Hossainpour, Reza (The University of Bergen, 2013)
Gas hydrate is a solid state of gas and water at high pressure and low temperature conditions. Vast energy potential is associated with gas hydrates and extensive on-going research aims at addressing the technical viability of production from hydrate deposits. Two different approaches to produce natural gas from hydrate reservoir have been proposed. Either decompose the hydrate by altering thermodynamic conditions or expose the hydrate to a thermodynamically more stable hydrate former inducing a replacement process of the encaged CH4 molecule in the lattice structure with the introduced new hydrate former. The latter has gained recent attention both in research and industrial communities. CO2 is an attractive candidate for such process due to both offering a better hydrate stability and possibilities for sequestrating a climate gas as gas hydrates in the earth. The work presented in this thesis is a series of experiments which studied processes involved during hydrate formation and hydrate dissociation within porous rocks. Methane hydrate was successfully and repeatedly formed within Bentheim sandstone core samples. The generated PVT-data were used to estimate the amount of methane stored in hydrate, the amount of free methane in the pores as well as the post hydrate formation water saturation. A comparison of data acquired in this study with in-house data demonstrated a trend towards higher post hydrate formation water saturation for increased initial water saturation and higher brine salinity. A number of experiments were conducted to study hydrate dissociation based production methods. Depressurization as a production method was investigated and production data acquired were compared with numerical simulation results acquired using TOUGH + HYDRATE. Thermal stimulation was investigated where temperature of the hydrate system was increased stepwise in order to find the dissociation threshold temperature at the experimental conditions. These data were later used to test the hydrate stability calculator CSMGem. ...